Lives and Livelihoods: How Socioeconomic Realities Shape Community Participation in Managing the Tanguar Haor Wetlands in Bangladesh - Salam, Mohammad Fakhrus (Research in Social Sciences and Technology, 2025)
This study delves into how local communities engage in the management of Tanguar Haor, a vital wetland in northeastern Bangladesh designated as an Ecologically Critical Area (ECA) and a Ramsar site. The study looks at relationships between important socioeconomic factors like income, education, age, gender, and local participation in wetland governance using household-level data from twelve villages. Employing a mixed-methods approach, the study integrates quantitative household survey data with qualitative interviews and focus group discussions to capture both statistical trends and community perceptions regarding participation in wetland governance. Roles in decision-making, project implementation, evaluation, and benefit-sharing procedures are among them. In contrast to their mainland counterparts in the Sunamganj district, the Tanguar Haor region, which has been inhabited for generations, is home to communities primarily impoverished and socioeconomically marginalized. The degree of meaningful participation is nonetheless unequal and frequently limited by structural inequities, despite the government's efforts to promote a co-management model incorporating governmental actors and local communities. The study finds that while the most underprivileged groups continue to be under-represented, those with greater socioeconomic status are substantially more involved in wetland management. These results emphasise how crucial it is to address socioeconomic inequality in order to promote inclusive and sustainable wetland governance. The study contributes to the broader discourse on environmental justice, local stewardship, and the role of equity in natural resource management.